Perception of Radiologists about Diagnostic Errors in Radiology in Yemen - Aklan H.M. (Yemeni Journal for Medical Sciences, 2014)
Background: Errors of diagnosis in Radiology are common, which affect patient’s care and management. Several types of radiological errors such as misperception, miscommunication, and procedure misconduct have been reported highlighting the importance of Radiologists’ awareness about their own errors. However, no data are available from Yemen. The aim of this study is to assess radiological errors in Yemen. Method: A standard questionnaire of radiological errors was distributed conveniently to radiologists in the main public and private hospitals in Sana'a city, Yemen. Results: Of 80 questionnaires distributed, 58 were returned back (the response rate was 72.5%). About 88% participants had diagnostic errors in 2013. The radiology errors were classified as under-call (false negative) (29.3%), communication errors (27.6%), overcall (false positive) (25.9%), procedural complication (24.1%) and interpretation errors (15.5%). Lack of previous studies and inadequate clinical information were mentioned as causes’ errors (37.9% and 36.2%, respectively). Most radiologists (70.7%) did not keep record for their own errors, and only 24.1% of radiologists had errors meeting in their departments. Conclusion: It has been concluded that errors in radiology are still a significant problem affecting patient safety. Collaborative efforts must be established to reduce diagnostic errors in radiology through organizing regular meetings to educate radiologists about such matter and create a good environment for learning and improvement rather than blaming and embarrassing.